Handbook of Climate Change Communication: Vol. 3 Case Studies in Climate Change Communication (Climate Change Management,, 2018)
This comprehensive handbook provides a unique overview of the theory, methodologies and best practices in climate change communication from around the world. It fosters the exchange of information, ideas and experience gained in the execution of successful projects and initiatives, and discusses novel methodological approaches aimed at promoting a better understanding of climate change adaptation. Addressing a gap in the literature on climate change communication and pursuing an integrated approach, the handbook documents and disseminates the wealth of experience currently available in this field. Volume 3 of the handbook provides case studies from around the world, documenting and disseminating the wealth of experiences available. .